2020
DOI: 10.1016/j.yhbeh.2019.104608
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mediates seasonal transitions in aggressive behavior and circulating androgen profiles in male Siberian hamsters

Abstract: Some seasonally-breeding animals are more aggressive during the short, "winter-like" days (SD) of the non-breeding season, despite gonadal regression and reduced circulating androgen levels. While the mechanisms underlying SD increases in aggression are not well understood, previous work from our lab suggests that pineal melatonin (MEL) and the adrenal androgen dehydroepiandrosterone (DHEA) are important in facilitating non-breeding aggression in Siberian hamsters (Phodopus sungorus). To characterize the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 105 publications
8
29
0
Order By: Relevance
“…More importantly, it is not the presence of melatonin per se, but the precise timing of melatonin that is critical for allowing individuals to integrate aspects of their environment and make seasonally appropriate adjustments in these neuroendocrine processes. These findings are in agreement with our previous work in male Siberian hamsters, in which we showed that administering timed melatonin to LD males induces gonadal regression, elevates aggressive behaviour and produces SD‐like changes in circulating androgen profiles 40 . It is also likely that this mode of integration for melatonin is involved in the regulation of aggression in other vertebrate species 17,18 , 63‐67.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…More importantly, it is not the presence of melatonin per se, but the precise timing of melatonin that is critical for allowing individuals to integrate aspects of their environment and make seasonally appropriate adjustments in these neuroendocrine processes. These findings are in agreement with our previous work in male Siberian hamsters, in which we showed that administering timed melatonin to LD males induces gonadal regression, elevates aggressive behaviour and produces SD‐like changes in circulating androgen profiles 40 . It is also likely that this mode of integration for melatonin is involved in the regulation of aggression in other vertebrate species 17,18 , 63‐67.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we have shown that short‐term exogenous melatonin treatment induces SD‐like increases in aggression in male and female hamsters, yet does not affect reproductive physiology or circulating gonadal steroid levels 16,38,39 . Conversely, long‐term administration of melatonin induces gonadal regression, elevates aggressive behaviour, and produces SD‐like changes in circulating androgen profiles in male hamsters 40 ; suggesting that melatonin may be involved in the early onset of responding to changes in ambient day length (eg, the transition from ‘spring’ to ‘fall’). Moreover, we have shown that melatonin acts directly on the adrenal glands to increase the release of DHEA in SD females, whereas melatonin acts directly on the ovaries to increase the release of DHEA in LD females 39 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations